Vision Zero - Coordinator (Qualification and Competence) - Alfredo Soeiro (2021)
Conference Aims Presentation of lessons learned from the COVID-19 pandemic for the construction sector. Highlighting the importance of the implementation of the Vision Zero Strategy as well as the role of the project players though practical solutions Presentation of new tools developed for the implementation of the Vision Zero Strategy and the Seven Golden Rules. Highlighting the importance of introducing digitalisation in the construction sector. Presentation of new technologies, and smart solutions for the transformation of the construction sector in the new digital age. Presentation of international examples and applications to integrate Health and Safety in Building Information Modelling (BIM). Highlighting the importance of investing in people, education and the prevention communication. International exchange of experience, knowledge and concerns. Participants' active involvement in the workshops of the Conference The Conference is Addressed to Civil Engineers - Architects - Construction Safety and Health Coordinators - Project Managers - Mechanical Engineers - Electrical Engineers - Safety and Health Officers and Inspectors - Prevention Consultants involved in the design and execution stage of construction projects - Contractors - Professionals who are interested to learn about health and safety issues in construction projects and the latest development on these issues - Interested citizens Language Greek and English with simultaneous translation Exhibition Companies that specialize in supplying Specialized Work Equipment, in providing training as well as other services related to construction safety and health, will exhibit innovative products and practical solutions and will present their services.